Nilai-Nilai Moral pada Cerita Rakyat Desa Rantau Kalis dan Implementasi di SMA Karya Budi - Adriana, Betania Clara; Thamimi, Muhammad; Sulastri, Saptiana (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research describes the moral values in the folk tales of Rantau Kalis Village and their implementation in Indonesian language learning at Karya Budi High School, Kapuas Hulu Regency. This study uses a descriptive qualitative method with a sociological literature approach. Data were collected through direct communication, recording, observation, and documentary study techniques, using interview guides, recording devices, observation guides, and the researcher as the instrument. The results of the study show that moral values related to God are found in the stories